Selenium (Molecular and Integrative Toxicology,, 2018)
This book summarizes the fast-growing and current knowledge about selenium interaction with cancer, diabetes, neuro-degeneration, heart disease, muscle disorders, HIV and several more. A special focus will be placed on in-depth knowledge about gene expression, selenoprotein biosynthesis, seleno-metabolism--as well as the molecular pathways, physiological roles, and the molecular action of selenium including interaction with other elements and vitamins or as Se-nanoparticles. The reader will receive the newest information regarding redox status and redox regulatory systems, specifically in relation to different glutathione peroxidases and thioredoxin-reductases as well as about cellular bioavailability and cytotoxicity, de-balanced immune response, inflammation or dietary aspects.